Composite fiber diaphragm for alkaline electrolytic cell and preparation method of composite fiber diaphragm

Through electrospinning technology, polymer polymers and hydrophilic nanoparticles are uniformly dispersed in the separator for alkaline electrolytic cells, which solves the problems of complex preparation process and insufficient performance of the existing separator, and achieves efficient and economical alkaline electrolytic cell separator preparation, improving the electrolytic efficiency and hydrophilicity of the separator.

CN119663370AActive Publication Date: 2025-03-21HUADIAN HEAVY IND CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411871112.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The preparation process of existing alkaline electrolytic cells is complicated, and it requires adding pore-generating agents and will produce a large amount of wastewater. The separator has poor performance and insufficient hydrophilicity, resulting in large resistance and low electrolytic efficiency.

Method used

Electrospinning technology is used to uniformly disperse polymer and hydrophilic nanoparticles on the polymer fabric substrate to prepare a composite fiber separator for alkaline electrolytic cells. This method does not require additional pore-generating agents and non-solvent phases, reducing wastewater generation and simplifying the preparation process.

Benefits of technology

The prepared composite fiber diaphragm has good mechanical properties, hydrophilicity and chemical stability, which reduces the membrane surface resistance, improves the electrolytic efficiency, and is simple in the preparation process and saves costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663370A_ABST
    Figure CN119663370A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of alkaline electrolytic water hydrogen production, in particular to a composite fiber diaphragm for an alkaline electrolytic bath and a preparation method of the composite fiber diaphragm. The preparation method of the composite fiber diaphragm for the alkaline electrolytic cell comprises the following steps: uniformly mixing a high-molecular polymer, hydrophilic nanoparticles and a solvent to obtain an electrostatic spinning precursor solution; the solvent comprises a first solvent; the first solvent comprises an amide organic solvent or / and a pyrrolidone organic solvent; and depositing the electrostatic spinning precursor solution on a polymer fabric substrate through electrostatic spinning treatment to prepare the composite fiber diaphragm for the alkaline electrolytic cell. According to the invention, hydrophilic nanoparticles are uniformly dispersed on high-molecular polymer nanowires and are attached to the surface of a polymer fabric substrate by using an electrostatic spinning technology to prepare the composite fiber diaphragm for the alkaline electrolytic cell, which is good in mechanical property, high in hydrophilicity and stable in chemical property, and the composite fiber diaphragm can be applied to the alkaline electrolytic cell to reduce energy consumption, reduce diaphragm surface resistance and improve the service life of the diaphragm. The electrolysis efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen production by alkaline water electrolysis, and in particular to a composite fiber diaphragm for an alkaline electrolytic cell and a preparation method thereof. Background Art

[0002] Hydrogen energy has been recognized as a zero-emission, zero-pollution clean energy carrier due to its high energy density, wide sources, and clean and pollution-free advantages. More and more countries regard the development of hydrogen energy as an important part of energy development. Hydrogen energy can be divided into green hydrogen, gray hydrogen, blue hydrogen, and purple hydrogen according to different production methods. Among them, green hydrogen is generated by renewable clean energy such as wind power or solar energy, and then this clean electricity is used to produce hydrogen by electrolysis of water. Green hydrogen basically does not produce greenhouse gases during the production process and is the main trend of hydrogen energy development at present.

[0003] According to the working principle, temperature and the electrolytic cell materials used, hydrogen production by water electrolysis can be divided into three categories: alkaline water electrolysis, proton exchange membrane water electrolysis, and high-temperature solid oxide water electrolysis. Alkaline water electrolysis technology is highly mature and has cost advantages. It is the main solution for existing large-scale green hydrogen engineering projects. Among them, the diaphragm is the key material of the alkaline electrolyzer. The diaphragm separates the electrolytic cell into the cathode and anode chambers, respectively performing reduction and oxidation reactions, and preventing the generated H2 and O2 from mixing. Asbestos diaphragm was the earliest commercial alkaline electrolyzer diaphragm material, but because it is a carcinogen, it has been gradually replaced by polymer diaphragms.

[0004] Polymer diaphragms have the advantages of good conductivity, strong chemical stability, and superior mechanical properties. They are very promising alkaline water electrolysis diaphragm materials, but polymer diaphragms generally have the problem of poor hydrophilicity. For example, polyphenylene sulfide (PPS) is the key component of the commercial alkaline electrolyzer diaphragm Zirfon. Due to the presence of benzene rings and sulfide bonds in its molecular structure, it has a certain flexibility and has good thermal stability, corrosion resistance, mechanical properties and chemical stability under high temperature conditions. It is a very promising polymer diaphragm material. However, the hydrophilicity of PPS fabric is poor, resulting in a large resistance as a diaphragm and low electrolysis efficiency in the electrolyzer. Therefore, how to improve the hydrophilicity of PPS diaphragms is still a problem that needs to be solved urgently.

[0005] In addition, the current process of preparing diaphragms through phase inversion is relatively complicated. In addition to effective materials such as PPS, polysulfone and inorganic nanoparticles, porogens need to be added. In addition, a large amount of water is required during the phase inversion process, which will produce a large amount of wastewater. Moreover, the diaphragms prepared by phase inversion tend to become brittle in a dry state and have poor flexibility, and usually need to be kept moist. Summary of the invention

[0006] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the existing alkaline electrolytic cell diaphragm, such as the complex preparation process, the need to add porogens, the generation of a large amount of wastewater and the poor performance of the diaphragm, thereby providing a composite fiber diaphragm for an alkaline electrolytic cell and a preparation method thereof that solves the above problems.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a composite fiber diaphragm for an alkaline electrolytic cell, comprising:

[0009] The high molecular weight polymer, the hydrophilic nanoparticles and the solvent are mixed to obtain an electrospinning precursor solution; the solvent includes a first solvent; the first solvent includes an amide organic solvent and / or a pyrrolidone organic solvent;

[0010] The electrospinning precursor solution is deposited on a polymer fabric substrate through electrospinning to prepare a composite fiber diaphragm for an alkaline electrolytic cell.

[0011] Preferably, the high molecular polymer includes at least one of polysulfone (PSF), polybenzimidazole (PBI), and sulfonated polyetheretherketone;

[0012] And / or, the amide organic solvent includes at least one of N,N-dimethylformamide (DMF) and N,N-dimethylacetamide (DMAc);

[0013] And / or, the pyrrolidone organic solvent includes N-methylpyrrolidone (NMP);

[0014] And / or, acetone is further added to the solvent;

[0015] And / or, a cosolvent is further added to the solvent. This is because high molecular polymers (especially polybenzimidazole) generally have a highly rigid and stable structure, and adding a cosolvent can make it dissolve in the solvent faster and more easily.

[0016] Preferably, the mass ratio of the first solvent to acetone in the solvent is 1:(0.05-0.2);

[0017] and / or, the co-solvent comprises lithium chloride;

[0018] And / or, the mass of the co-solvent is 1-5wt% of the mass of the solvent, preferably 3wt%.

[0019] Preferably, the material of the polymer fabric substrate includes at least one of polyphenylene sulfide (PPS), polytetrafluoroethylene (PTFE), polypropylene (PP), polyimide (PI), and polybenzimidazole (PBI).

[0020] Preferably, the hydrophilic nanoparticles include at least one of nano zirconium dioxide particles, nano silicon dioxide particles, nano cerium dioxide particles, nano titanium dioxide particles, and nano aluminum oxide particles.

[0021] Preferably, the mass ratio of the high molecular weight polymer, the hydrophilic nanoparticles and the solvent is (1-2):(1-2):(6-14), preferably 1:2:6.

[0022] Preferably, the process of obtaining the electrospinning precursor solution comprises: mixing a high molecular weight polymer with a solvent to obtain a high molecular weight polymer dispersion; and uniformly mixing the high molecular weight polymer dispersion with hydrophilic nanoparticles to obtain the electrospinning precursor solution.

[0023] Preferably, the electrospinning process is a double-sided electrospinning process.

[0024] Preferably, the parameters of the electrospinning process are: voltage of 10-20 kV, distance from needle tip to roller of 15-25 cm, and feed flow rate of electrospinning precursor solution of 1-2 ml / h;

[0025] And / or, after the electrospinning treatment, a drying treatment is further performed.

[0026] Preferably, the drying treatment is to place in dry air for 24 hours to remove residual solvent.

[0027] In a second aspect, the present invention further provides a composite fiber diaphragm for an alkaline electrolytic cell, which is prepared by the above-mentioned method for preparing the composite fiber diaphragm for an alkaline electrolytic cell.

[0028] The technical solution of the present invention has the following advantages:

[0029] A method for preparing a composite fiber diaphragm for an alkaline electrolytic cell comprises: mixing a high molecular polymer, hydrophilic nanoparticles and a solvent to obtain an electrospinning precursor solution; the solvent comprises a first solvent; the first solvent comprises an amide organic solvent or / and a pyrrolidone organic solvent; and depositing the electrospinning precursor solution on a polymer fabric substrate (e.g., a polyphenylene sulfide fabric substrate) through an electrospinning process to obtain a composite fiber diaphragm for an alkaline electrolytic cell. The present invention utilizes electrospinning technology to evenly disperse hydrophilic nanoparticles on nanowires formed by high molecular polymers and attach them to the surface of the polymer fabric substrate, thereby preparing a composite fiber diaphragm for an alkaline electrolytic cell with good mechanical properties, high hydrophilicity and stable chemical properties. The composite fiber diaphragm for an alkaline electrolytic cell can be used in an alkaline electrolytic cell to reduce the surface resistance of the diaphragm and improve the electrolysis efficiency. Compared with the diaphragm prepared by the ordinary phase inversion method, the raw materials used in the present invention are simple, the preparation process is simple, no additional pore-forming agent / porogen and non-solvent phase need to be added, and there is no need to treat a large amount of wastewater, thus saving costs. At the same time, the internal morphology of the composite fiber diaphragm prepared by the present invention is nanofiber, which has a high specific surface area and porosity, can increase the doping content of hydrophilic nanoparticles, reduce the agglomeration of hydrophilic nanoparticles, and make the diaphragm have more hydrophilic sites, thereby improving the hydrophilicity of the diaphragm.

[0030] In addition, the fiber membrane prepared by electrospinning has better flexibility and is not easy to break or fall off after bending, making it easy to store and transport. However, the membrane prepared by phase inversion tends to become brittle in a dry state and usually needs to be kept moist. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 It is a schematic diagram of the preparation process of the composite fiber diaphragm for the alkaline electrolytic cell according to Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0034] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0035] Example 1

[0036] This embodiment provides a method for preparing a composite fiber diaphragm for an alkaline electrolytic cell. The schematic diagram of the preparation process is shown in FIG. Figure 1 As shown, the specific steps are as follows:

[0037] 1) Obtaining an electrospinning precursor solution: First, 1 g of polysulfone (PSF) was mixed with 6 g of a solvent (a mixed solvent of N,N-dimethylformamide and acetone in a mass ratio of 1:0.1), and mechanically stirred until completely dissolved to form a transparent solution; then, 2 g of nano zirconium dioxide particles (ZrNP) were added in 4 portions, and stirred continuously to prevent the nanoparticles from agglomerating, and finally a uniform precursor solution was formed, which was allowed to stand for 12 h to remove bubbles, thereby obtaining an electrospinning precursor solution;

[0038] 2) The electrospinning precursor solution prepared in step 1) is loaded into an electrospinning syringe, and the polyphenylene sulfide (PPS) fabric is attached to a roller for double-sided electrospinning; the electrospinning parameters are: voltage 15KV, distance from needle tip to roller 15cm, feed rate 1.5ml / h; after spinning, the diaphragm is removed and dried in dry air for 24h to remove residual solvent, thereby obtaining a composite fiber diaphragm for an alkaline electrolytic cell.

[0039] Example 2

[0040] This embodiment provides a method for preparing a composite fiber diaphragm for an alkaline electrolytic cell, and the specific steps are as follows:

[0041] 1) Obtaining an electrospinning precursor solution: first, 1 g of polybenzimidazole was mixed with 6 g of a solvent (a solution of N,N-dimethylacetamide containing 3 wt% LiCl), and mechanically stirred at 120° C. until the polymer was completely dissolved, and the solution was centrifuged to remove insoluble impurities, and the supernatant was taken; then, 2 g of nano-titanium dioxide particles were added three times, and stirred continuously to prevent the nano-particles from agglomerating, and finally a uniform precursor solution was formed, and the solution was allowed to stand for 12 hours to remove bubbles, thereby obtaining an electrospinning precursor solution;

[0042] 2) The electrospinning precursor solution prepared in step 1) is loaded into an electrospinning syringe, and the polyphenylene sulfide fabric is attached to a roller for double-sided electrospinning; the electrospinning parameters are: voltage 20KV, distance from needle tip to roller 25cm, feed rate 2ml / h; after spinning, the diaphragm is removed and dried in dry air for 24h to remove residual solvent, thereby obtaining a composite fiber diaphragm for an alkaline electrolytic cell.

[0043] Example 3

[0044] This embodiment provides a method for preparing a composite fiber diaphragm for an alkaline electrolytic cell, and the specific steps are as follows:

[0045] 1) Obtaining an electrospinning precursor solution: first, sulfonating polyetheretherketone with sulfuric acid to make it soluble; mixing 1 g of sulfonated polyetheretherketone with 6 g of N,N-dimethylformamide, and mechanically stirring until the polymer is completely dissolved; then adding 2 g of nano-alumina particles in 4 portions, and stirring continuously to prevent the nano-particles from agglomerating, and finally forming a uniform precursor solution, which was allowed to stand for 12 hours to remove bubbles, to obtain an electrospinning precursor solution;

[0046] 2) The electrospinning precursor solution prepared in step 1) is loaded into an electrospinning syringe, and the polypropylene fabric is attached to a roller for double-sided electrospinning; the electrospinning parameters are: voltage 15KV, distance from needle tip to roller 15cm, feed rate 1ml / h; after spinning, the diaphragm is removed and dried in dry air for 24h to remove residual solvent, thereby obtaining a composite fiber diaphragm for an alkaline electrolytic cell.

[0047] Example 4

[0048] This embodiment provides a method for preparing a composite fiber diaphragm for an alkaline electrolytic cell, and the specific steps are as follows:

[0049] 1) Obtaining an electrospinning precursor solution: 1 g of polysulfone, 6 g of a solvent (a mixed solvent of N,N-dimethylformamide and acetone in a mass ratio of 1:0.1), and 2 g of nano zirconium dioxide particles were mixed at the same time, mechanically stirred for more than 24 hours until a uniform precursor solution was formed, and allowed to stand for 12 hours to remove bubbles, thereby obtaining an electrospinning precursor solution;

[0050] 2) The electrospinning precursor solution prepared in step 1) is loaded into an electrospinning syringe, and the polyphenylene sulfide (PPS) fabric is attached to a roller for double-sided electrospinning; the electrospinning parameters are: voltage 15KV, distance from needle tip to roller 15cm, feed rate 1.5ml / h; after spinning, the diaphragm is removed and dried in dry air for 24h to remove residual solvent, thereby obtaining a composite fiber diaphragm for an alkaline electrolytic cell.

[0051] Example 5

[0052] This embodiment provides a method for preparing a composite fiber diaphragm for an alkaline electrolytic cell. The difference from Embodiment 1 is that the solvent is N,N-dimethylformamide, that is, a single solvent is used, and other conditions are the same as those in Embodiment 1.

[0053] Example 6

[0054] This embodiment provides a method for preparing a composite fiber diaphragm for an alkaline electrolytic cell. The difference from Embodiment 1 is that N,N-dimethylformamide is replaced by N-methylpyrrolidone, and other conditions are the same as those in Embodiment 1.

[0055] Comparative Example 1

[0056] This comparative example provides a method for preparing a composite diaphragm for an alkaline electrolytic cell, and the specific steps are as follows:

[0057] 1) Obtaining a casting solution: First, 3 g of polysulfone (PSF) was mixed with 11 g of N-methylpyrrolidone, and the mixture was mechanically stirred until it was completely dissolved to form a transparent solution; then, 3 g of polyvinylpyrrolidone pore-forming agent was added, and stirring was continued until the solvent was fully dissolved; then, 3 g of nano zirconium dioxide particles (ZrNP) were added in three portions, and mechanical stirring was performed for 24 h to form a uniform solution, and the mixture was stirred at a low speed or allowed to stand for 12 h to remove bubbles, thereby obtaining a phase inversion casting solution;

[0058] 2) Pour the above-mentioned casting liquid onto a flat glass plate, adjust the thickness with a film scraper and then scrape it into a film, let it stand in the air for 30 seconds for pre-evaporation, then place the entire glass plate in deionized water for phase inversion, and after 10 minutes, the casting liquid solidifies and falls off the glass plate to obtain a composite diaphragm.

[0059] 3) Soak the above diaphragm in deionized water for 20 minutes to further precipitate the residual solvent. Repeat the soaking for 2-3 times, take out the composite diaphragm, and dry it in a clean room for more than 24 hours to obtain a comparative composite diaphragm.

[0060] Comparative Example 2

[0061] This comparative example provides a method for preparing a composite fiber diaphragm for an alkaline electrolytic cell, which is different from Example 1 in that the solvent is acetone, that is, a single solvent is used, and other conditions are the same as those in Example 1. In this comparative example, since acetone cannot dissolve the high molecular weight polymer, the electrospinning precursor solution cannot be obtained, and thus subsequent operations cannot be performed, and the composite fiber diaphragm for an alkaline electrolytic cell cannot be prepared.

[0062] Test Example 1

[0063] This test example performs performance tests on the composite diaphragm samples for alkaline electrolytic cells prepared in the above embodiments and comparative examples. The test results are shown in Table 1 below.

[0064] Among them, the contact angle testing method is: using deionized water as a medium to test the contact angles of the above-mentioned example samples and comparative samples, the instrument used is Chengde Dingsheng JY-82C contact angle tester, and the testing steps are as follows: at room temperature, the prepared diaphragm is cut into samples with a length and width of 20 mm × 20 mm, placed on the JY-82 contact angle testing platform, the sample is kept flat, and water drops are dripped using the automatic titration system of the equipment, test photos are taken, the droplet shape curve in the image is fitted, and the contact angle is calculated.

[0065] Porosity test method: The porosity is tested by soaking in n-butanol. The membrane is cut into 20mm×20mm samples and soaked in n-butanol for 2h. After taking it out, the liquid on the surface of the membrane is wiped dry with a test paper. The porosity is calculated after weighing the mass. Three groups of parallel measurements are used for each sample, and the average value is taken. The porosity calculation formula is: Porosity = (W1-W0) / ρV0×100%; where W1 and W0 are the mass of the polymer membrane before and after soaking in n-butanol (mg), and ρ is the density of n-butanol (mg / cm 3 ), V0 is the volume of the membrane before immersion in n-butanol (cm 3 ).

[0066] Specific surface area test method: The specific surface area of ​​the membrane is tested by nitrogen isothermal desorption experiment. The details are as follows: take about 50-100 mg of sample and put it into the test bottle for degassing pretreatment for 12 hours to remove the moisture and adsorbed gas in the sample, and then perform nitrogen adsorption and desorption test under low temperature liquid nitrogen, and calculate the specific surface area of ​​the membrane by multi-point Brunauer-Emmett-Teller (BET) method.

[0067] Tensile strength test method: The tensile strength of the film was tested using an electronic universal material testing machine. The diaphragm was cut into samples of size 40 mm × 10 mm for tensile testing. The tensile rate was 10 mm / min, the clamping distance was 20 mm, and each sample was tested in 3 groups in parallel to take the average value.

[0068] Surface resistance test method:

[0069] 1) Cut the diaphragm into 5 samples of 2.5 cm×6 cm and soak them in a 30% potassium hydroxide solution for more than 4 hours.

[0070] 2) Inject the alkaline solution into the resistance test tank, assemble two test fixtures, put them into the resistance test tank filled with electrolyte, connect the electrodes, and test the solution resistance without a diaphragm;

[0071] 3) Assemble the diaphragm sample into the test fixture and test the total resistance of the solution and the diaphragm after adding the diaphragm;

[0072] 4) The average value of the surface resistance test results of the five samples is taken as the measured value of the diaphragm surface resistance.

[0073] Table 1

[0074]

[0075]

[0076] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a composite fiber diaphragm for an alkaline electrolytic cell, characterized in that: include: The high molecular weight polymer, the hydrophilic nanoparticles and the solvent are mixed to obtain an electrospinning precursor solution; the solvent includes a first solvent; the first solvent includes an amide organic solvent and / or a pyrrolidone organic solvent; The electrospinning precursor solution is deposited on a polymer fabric substrate through electrospinning to prepare a composite fiber diaphragm for an alkaline electrolytic cell.

2. The preparation method according to claim 1, characterized in that: The high molecular polymer includes at least one of polysulfone, polybenzimidazole, and sulfonated polyetheretherketone; And / or, the amide organic solvent includes at least one of N,N-dimethylformamide and N,N-dimethylacetamide; And / or, the pyrrolidone organic solvent includes N-methylpyrrolidone; And / or, acetone is further added to the solvent; And / or, a co-solvent is further added to the solvent.

3. The preparation method according to claim 2, characterized in that: The mass ratio of the first solvent to acetone in the solvent is 1:(0.05-0.2); and / or, the co-solvent comprises lithium chloride; And / or, the mass of the co-solvent is 1-5wt% of the mass of the solvent, preferably 3wt%.

4. The preparation method according to any one of claims 1 to 3, characterized in that The material of the polymer fabric substrate includes at least one of polyphenylene sulfide, polytetrafluoroethylene, polypropylene, polyimide and polybenzimidazole.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The hydrophilic nanoparticles include at least one of nano zirconium dioxide particles, nano silicon dioxide particles, nano cerium dioxide particles, nano titanium dioxide particles, and nano aluminum oxide particles.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The mass ratio of the high molecular weight polymer, the hydrophilic nanoparticles and the solvent is (1-2):(1-2):(6-14), preferably 1:2:

6.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The process of obtaining the electrospinning precursor solution includes: mixing a high molecular polymer with a solvent to obtain a high molecular polymer dispersion; and uniformly mixing the high molecular polymer dispersion with hydrophilic nanoparticles to obtain the electrospinning precursor solution.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The electrospinning process is a double-sided electrospinning process.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The parameters of the electrospinning process are: voltage of 10-20 kV, distance from needle tip to roller of 15-25 cm, and feed flow rate of electrospinning precursor solution of 1-2 ml / h; And / or, after the electrospinning treatment, a drying treatment is further performed.

10. A composite fiber diaphragm for an alkaline electrolytic cell, characterized in that: The composite fiber diaphragm is prepared by the method for preparing the composite fiber diaphragm for alkaline electrolytic cell according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of modified diaphragm for lithium-ion secondary battery as well as product and preparation device thereof

    CN102218871A

  • Preparation method of para-aramid polymer membrane, prepared through electrospinning method, for lithium-ion battery

    CN108666501A

  • Electrolytic cell composite diaphragm, preparation method, alkaline water electrolysis hydrogen production device and application

    CN114774988A

  • Isolating membrane for alkaline electrolyzed water electrolyzer and preparation method of isolating membrane

    CN117210871A

  • Dry alkaline water electrolyser diaphragm and preparation method thereof

    CN117512690A